Estudio de prefactibilidad para la instalación de una planta productora y comercializadora de snack de aguaymanto deshidratado - Ballenas Valencia, Diego Alejandro (2023)
The creation of a plant that dehydrates aguaymanto is an alternative that offers customers a long-lasting product while maintaining its nutritional values and organoleptic characteristics, thus achieving better quality and better prices. The present research work seeks to study the feasibility of the installation of a processing plant of dehydrated aguaymanto snack by applying the knowledge learned during the university stage. It will develop the problems that the fruit has in Peru, as well as the benefits of dehydrated aguaymanto. Also, the objectives and scope of the research will be explained. Second, the project's demand for the first year is 261 tons of fresh aguaymanto, which was projected using the linear regression method. Based on the results of the surveys carried out, the target public was determined to be people 13 years of age and older who belong to SES B and C. Third, the plant location is in Ate, Lima Metropolitana, which was determined using the factor ranking method. Fourth, the proposed production process for the manufacture of the dehydrated aguaymanto snack consists of the following stages: weighing, selection, removal of the cap, disinfection, rinsing, dehydration, inspection, vacuum packaging, labeling and boxing, the main raw material being fresh aguaymanto. The plant has an installed plant capacity of 74.63 tons of aguaymanto per year, which was defined by the dehydration activity that is the bottleneck for the process. The total area proposed is 332 m2. Finally, the project investment amounts to S/ 2 422 829,79 and has a financing structure of 70% debt and 30% equity. The debt will be financed by BCP. The economic and financial evaluation of the project is also carried out. The economic flow reveals an IRR of 24% with a payback period of 04 years, 09 months and 05 days, while the financial flow reveals an IRR of 31% with a payback period of 04 years, 08 months and 01 day.